1967
DOI: 10.1021/ed044p409
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion of gases: A physical chemistry experiment

Abstract: In the procedure the progress of diffusion is determined by measuring the change in conductivity over time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
5
1

Year Published

1969
1969
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 0 publications
3
5
1
Order By: Relevance
“…For the (C 2 H 6 + C 3 H 8 ) system, the two available experimental data sets , agree very satisfactorily with the calculated values. The datum of Gover at room temperature (the exact temperature is not specified in the paper but is assumed to be 298.15 K) deviates from the calculated value by −1.4%, while the three data points of Gotoh et al agree even within 0.9% with our values.…”
Section: Results and Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…For the (C 2 H 6 + C 3 H 8 ) system, the two available experimental data sets , agree very satisfactorily with the calculated values. The datum of Gover at room temperature (the exact temperature is not specified in the paper but is assumed to be 298.15 K) deviates from the calculated value by −1.4%, while the three data points of Gotoh et al agree even within 0.9% with our values.…”
Section: Results and Discussionsupporting
confidence: 76%
“…For the (C 2 H 6 + C 3 H 8 ) system, the two available experimental data sets , agree very satisfactorily with the calculated values. The datum of Gover at room temperature (the exact temperature is not specified in the paper but is assumed to be 298.15 K) deviates from the calculated value by −1.4%, while the three data points of Gotoh et al agree even within 0.9% with our values. The data of Gotoh et al for the (CH 4 + C 2 H 6 ) and (CH 4 + C 3 H 8 ) systems (reported in the same paper) also agree well with the corresponding calculated values. , As one would expect, the values obtained with the unadjusted C 2 H 6 –C 3 H 8 PES deviate more significantly from the experimental data.…”
Section: Results and Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Watts described a class experiment consisting of the quantitative analysis of the total amount of a liquid diffused into a capillary containing another liquid (3). Finally Gover reported a study of gaseous diffusion performed by students; the concentration was measured in a gas chromatograph (4).…”
mentioning
confidence: 99%